Malaysia should seek help from UN to resolve crisis - News Straits, Times (New Strait Times, 2017)
KUALA LUMPUR: Malaysia should seek the United Nations' support to pressure Pyongyang to release Malaysians "held hostage" in North Korea and to avoid the diplomatic row from escalating, international relations and human rights experts say.